2008
DOI: 10.4314/tjpr.v7i4.14702
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Interaction of Crude Methanol Extract of <i>Garcinia kola</i> Seed with Gatifloxacin

Abstract: subtilis in ratios of 9(GAT):1(GKS) down to 6(GAT) :4(GKS) after which additivity, indifference and antagonism, in that order, were manifested as the ratio of GKS increased in the combination. Against S. aureus, the combined interaction showed a somewhat irregular pattern of effect, including synergism at GAT:GKS ratios of 9:1, 2:8 and 1:9 , antagonism at ratios of 8:2, 5:5 and 4:6 and indifference at GAT:GKS ratios of 7:3, 6:4 and 3:7. Conclusion:The results from this study suggest that the effect of combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…It is well demonstrated that the efflux pumps reduce the intracellular concentration of antibiotics and consequently their activities [ 57 ]. The MDR bacteria strains used in this paper are known for their ability to overexpress active efflux [ 58 ]. At MIC/2, synergistic effects were noted with the association of NOR, CHL, TET (on 100% the studied bacteria), ERY (on 80%), CIP (on 70%), and P. nitida extract meanwhile G. kola extract also increased the activity of NOR, TET (on 100%), ERY, and CIP (on 70%).…”
Section: Discussionmentioning
confidence: 99%
“…It is well demonstrated that the efflux pumps reduce the intracellular concentration of antibiotics and consequently their activities [ 57 ]. The MDR bacteria strains used in this paper are known for their ability to overexpress active efflux [ 58 ]. At MIC/2, synergistic effects were noted with the association of NOR, CHL, TET (on 100% the studied bacteria), ERY (on 80%), CIP (on 70%), and P. nitida extract meanwhile G. kola extract also increased the activity of NOR, TET (on 100%), ERY, and CIP (on 70%).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic Applications of Garcinia Kola: Antimicrobial Activity: Antimicrobial activities of crude extract of Garcinia kola against some bacterial isolates comprising of both Gram-positive and Gram-negative organisms had been reported 44 In another study, the antimicrobial interaction between G. kola seed and gatifloxacin, a fourthgeneration fluoroquinolone, was evaluated by a modification of the checkerboard technique 45 . The antimicrobial activity of five different solvent extracts of Garcinia kola seed had been investigated against 30 clinical strains of Helicobacter pylori and a standard control strain, NCTC 11638, using conventional microbiological techniques 46 .…”
Section: Fig 4: Some Chemical Constituents Of G Kolamentioning
confidence: 99%
“…The sap of G. kola is used for the treatment of parasitic skin diseases while the latex is orally ingested for the treatment of gonorrhoea. It is also useful in the eradication of guinea worm infestation (Ofakansi et al, 2008).…”
Section: Taxonomic Description Of Garcinia Kolamentioning
confidence: 99%